Novabot: a mini-blimp dedicated to stage recording (2024)
During a second-year internship at the Georges Charpak Provence campus of Mines SaintÉtienne, located in Gardanne, Provence, I collaborated with a final-year master’s engineering student, Thibault Langlart, within the Novabot project. This project aimed to integrate a floating drone called the "ID-FLY airship" into theatrical applications to provide a unique perspective of performance scenes. Working at the ID-Fab facility under the supervision of research engineer Francois Bernier and Dr. Julien Serres, we focused on automating the drone’s behavior to maintain a fixed distance from artists on stage. Our tasks included implementing the ROS framework on a Raspberry Pi, adapting the Luxonis AI camera as a position sensor, creating a dynamic model, and developing the flight control system. Additionally, we contributed to an artistic demonstration led by Ph.D. student Yousra Mansar, who is conducting artistic research as part of her thesis at LESA in Aix-en-Provence.